Monitoring the recovery-stress states of athletes: Psychometric properties of the acute recovery and stress scale and short recovery stress scale among Dutch and Flemish athletes - Brauers, J. J.; Den Hartigh, R. J. R.; Jakowski, S.; Kellmann, M.; Wylleman, P.; Lemmink, K. A. P. M.; Brink, M. S. (Journal of Sports Sciences, 2024)
The Acute Recovery and Stress Scale (ARSS) and the Short Recovery and Stress Scale (SRSS) are recently-introduced instruments to monitor recovery and stress processes in athletes. In this study, our aims were to replicate and extend previous psychometric assessments of the instruments, by incorporating recovery and stress dimensions into one model. Therefore, we conducted five confirmatory factor analyses (CFA) and determined structural validity, internal consistency, and construct validity. Dutch and Flemish athletes (N = 385, 213 females, 170 males, 2 others, 21.03 ± 5.44 years) completed the translated ARSS and SRSS, the Recovery Stress Questionnaire for Athletes (RESTQ-Sport-76), the Rating of Perceived Exertion (RPE) and the Total Quality of Recovery (TQR). There was a good model fit for the replicated CFA, sub-optimal model fit for the models that incorporated recovery and stress into one model, and satisfactory internal consistency (a=.75 - .87). The correlations within and between the ARSS and SRSS, as well as between the ARSS/SRSS and the RESTQ-Sport-76 (r = .31 - -.77 for the ARSS, r = .28 - -.63 for the SRSS), the RPE (r = .19 - -.23), and the TQR (r = .63 - -.63) also supported construct validity. The combined findings support the use of the ARSS and SRSS to assess stress and recovery in sports-related research and practice.